SISTEM INFORMASI PROGRAM MAHASISWA WIRAUSAHA UNIVERSITAS NEGERI PADANG - Wahidin Saputra; Elfi Tasrif (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
Entrepreneurship plays an important role in Indonesia's development. Entrepreneurship is important because of the magnitude of the role played by entrepreneurs in overcoming various problems of national economic development such as poverty alleviation, high unemployment, the Entrepreneurial Student Program is a program of the Ministry of Education and Culture's Directorate General of Higher Education implemented and developed by universities. Padang State University is one of the universities that has received assistance from the Directorate General of Higher Education. The Entrepreneurial Student Program Information System built has a web-based display, where with this information system students or other users can access anytime and anywhere to get information about the Entrepreneurial Student Program. For proposers, they can input their proposals directly through this information system and facilitate data storage for managers of the Entrepreneurial Student Program. This system is built using the Yii2 Framework, a component-based PHP programming that has high performance for large-scale web application development. Keywords: Information Systems, Entrepreneurial Student Programs, Yii2 Framework